2013
DOI: 10.1213/ane.0b013e31829cfd21
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of 2 Doses of Epidural Morphine for Postcesarean Delivery Analgesia

Abstract: When used as part of a multimodal analgesia regimen, 1.5 mg epidural morphine provided noninferior postcesarean analgesia and caused fewer adverse effects compared with 3 mg epidural morphine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 13 publications
0
26
0
1
Order By: Relevance
“…However, it is not only associated with side effects, including nausea, vomiting, pruritus and respiratory depression, but also with an analgesic ceiling effect (19). Singh et al (20) reported that compared with two 3-mg doses of epidural morphine, two 1.5-mg doses of epidural morphine produced equivalent effects on post-cesarean pain with fewer side effects, when used as part of a multimodal analgesia regimen. Epidural morphine alone is not sufficient Values are expressed as the mean ± standard deviation or n (%).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not only associated with side effects, including nausea, vomiting, pruritus and respiratory depression, but also with an analgesic ceiling effect (19). Singh et al (20) reported that compared with two 3-mg doses of epidural morphine, two 1.5-mg doses of epidural morphine produced equivalent effects on post-cesarean pain with fewer side effects, when used as part of a multimodal analgesia regimen. Epidural morphine alone is not sufficient Values are expressed as the mean ± standard deviation or n (%).…”
Section: Discussionmentioning
confidence: 99%
“…Twelve of the 32 units added morphine to the epidural local anaesthesia, the most common dose was 2 mg. Singh et al found epidural morphine at 1.5 mg provided none-inferior post caesarean analgesia and caused fewer adverse effects compared with 3 mg epidural morphine 20 . Still the majority of responding units decided not to add morphine in epidural analgesia for CS postoperative analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found the 1.5 mg of epidural morphine to be equally efficacious and associated with lower incidence of nausea and pruritus. [11]…”
Section: Intrathecal and Epidural Opioidsmentioning
confidence: 99%